2020
DOI: 10.1029/2019gb006508
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Diatom‐Bound Paleoproxy: Tracing the Isotopic Composition of Nutrient‐Nitrogen Into Southern Ocean Particles and Sediments

Abstract: Sedimentary nitrogen isotope (as δ 15 N) records from the Southern Ocean provide critical constraints on surface nutrient consumption in the past and the role of Southern Ocean biophysical changes in setting atmospheric pCO 2. We present a field assessment of how surface nitrate consumption is reflected in δ 15 N values of total nitrogen and diatom-bound nitrogen pools of particles and sediments across the Southern Ocean along 170°W during late austral summer. Mixed layer nitrate δ 15 N values increase northwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Palaeoceanographic proxies -NH₄⁺ cycling in the Southern Ocean mixed layer may be important for palaeoceanographic proxies (Smart et al, 2020;Robinson et al, 2020), such as those that use the 15 N of organic matter preserved in fossil foraminifer or diatom shells to infer the extent of upper ocean NO 3 consumption in the past (and by extension, the role of Southern Ocean biology in determining atmospheric CO 2 ; e.g., Martínez-García et al, 2014;Studer et al, 2015). A recent ground-truthing study from the Southern Ocean showed that the 15 N of foraminifer-bound organic N tracks the 15 N of PON rather than NO 3 - (Smart et al, 2020), in contrast to results from the low-latitude ocean (Ren et al, 2012;Smart et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Palaeoceanographic proxies -NH₄⁺ cycling in the Southern Ocean mixed layer may be important for palaeoceanographic proxies (Smart et al, 2020;Robinson et al, 2020), such as those that use the 15 N of organic matter preserved in fossil foraminifer or diatom shells to infer the extent of upper ocean NO 3 consumption in the past (and by extension, the role of Southern Ocean biology in determining atmospheric CO 2 ; e.g., Martínez-García et al, 2014;Studer et al, 2015). A recent ground-truthing study from the Southern Ocean showed that the 15 N of foraminifer-bound organic N tracks the 15 N of PON rather than NO 3 - (Smart et al, 2020), in contrast to results from the low-latitude ocean (Ren et al, 2012;Smart et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen (N) isotopic compositions of oceanic nitrate and bulk sediments are powerful indicators for evaluating surface nitrate utilization in the modern and past oceans, facilitating the understanding of spatial and temporal changes in the strength of the biological pump (Altabet and Francois 1994; Robinson et al 2020). The key to the application of stable N isotope tools is to understand the magnitude of the isotope effect (i.e., a phenomenon associated with the isotopes of a given element exhibiting different rates during reactions, which is reported as ε = ( light k / heavy k – 1) × 1000, expressed in ‰, in which k refers to the specific reaction rate constants of light and heavy isotopes) for nitrate assimilation.…”
mentioning
confidence: 99%